(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2024)
In this article, thoughts are expressed on the theory and practice of patriotic education in young people, their comprehensive training through the means of ART pedagogy ( the role of artistic literature, music, theater and cinema in youth education) to fulfill their duties in protecting the Republic of Uzbekistan-important tasks of pedagogical communities of the educational institution.